PSVII-6 Effects of 25-hydroxycholecalciferol supplementation on gene expression of feedlot cattle. (30th November 2020) - Martins, Tainá E; Acedo, Tiago S; Gouvea, Vinicius N; Vasconcellos, Guilherme S; Arrigoni, Mário B; Martins, Cyntia L; Millen, Danilo D; Pai, Maeli D; Perdigão, Alexandre; Melo, Gabriel F; Rizzieri, Ramon A; Rosolen, Leonardo M; et al.
Abstract: The objective was to evaluate the effects of 25-hydroxycholecalciferol (HyD ®, DSM Produtos Nutricionais Brasil S.A.) supplementation in expression of genes related to anabolism and catabolism of feedlot cattle. A total of 120 Nellore bulls (IBW = 370±20 kg) were distributed in 24 fully roofed-pens with concrete floor (5 animals/pen) in a randomized complete block design (8 pens/treatment). The treatments were T1 (control): no supplementation of HyD ® ; T2: HyD ® supplementation at 1 mg/animal/day; T3: HyD ® supplementation at 3 mg/animal/day. Basal diet was formulated to meet requirements of finishing bulls, considering an ADG of 1.6 kg/day (Level 2 Nutrition System, Fox et al., 2004). Adaptation to diets followed a step-up scheme for 14 days, with concentrate inclusion being gradually increased from 76 to 91% DM. Finishing diets were offered from 15th to 100th day of feedlot period and animals fed twice a day (0800 and 1500), with bunks managed for a maximum of 5% orts. After slaughter, muscle samples were collected for quantitative evaluation of gene expression using RT-qPCR method, considering the following genes: SOD1 (antioxidant marker), IGF1, IGF2 and MTOR (anabolism), FOXO1, MURF1, Atrogin-1 and MSTN (catabolism). Statistical analysis was performed using PROC MIXED of SAS® and means compared by Tukey test at 5% probability. No significant differences among treatments were observed for SOD1, FOXO1, MURF1 and Atrogin-1 expression (P >0.05). However, tendencies (0.05 > P ≤0.10) could be observed for IGF1, IGF2, MTOR and MSTN expression in animals receiving HyD ®, regardless of dosage. These results indicate a positive effect of HyD ® on muscular anabolism and protein synthesis on feedlot finishing cattle. Moreover, the greater expression on MSTN suggest a higher protein turnover and muscular growth regulation. In conclusion, HyD ® supplementation increased expression of genes correlated to muscular growth and protein synthesis, being a viable technology for beef cattle finished in feedlot systems.